Sprawność w języku polskim dwujęzycznej młodzieży pochodzenia polskiego mieszkającej w Anglii - Bernadeta Niesporek-Szamburska (Postscriptum Polonistyczne)
The author presents the results of a small survey into the Polish language skills of students of Polish origin residing in England. She starts by determining their level of language skills, then she compares the overall competences of young people born in England to those who came to the country a few years ago (competences are in terms of listening, reading comprehension and writing). The author analyzes in detail the results of the test and the effectiveness of the language teaching systems. The results allow her to draw a number of conclusions: the importance of bilingualism for children, that there is a rapid reduction in Polish language skills among adolescents who have come from Poland as well as the observation that for many children born overseas it is now too late to become fluent in their mother tongue.